Cerebral Malaria - Ali, Liaqat; Khan, Faiz Muhammad; Ahmad, Irshad (Journal of Postgraduate Medical Institute, 2011)
Malaria is one of the most infectious disease of man and is perhaps responsible for mare morbidity and economic losses than any other disease alone. It is produced by a parasite of class Sporozoa and genus Plasmodium. It has four species namely Vivax, Ovale, Falciparum and Malariae. Its vector is a female Anopheles mosquito, while its vertebrate host is man. Out of the four species of Plasmodium, falciparum is the most aggressive and produced a malignant disease characterized by high grade fever, extensive haemolysis, severe anaemia, jaundice and visceromegaly. Besides these, plasmodium falciparum has some special presentations like Black Water Fever, Transplacental Transmission and Cerebral Malaria. According to a World Health Organization report regarding World Malaria Situation in 1990, the global incidence of malaria is 120 million cases each year, out of which more than a million die annually. Majority of the victims are children and cerebral malaria is the main culprit. Many workers like Phillips and Solmon believe that cerebral malaria is invariably lethal if left untreated. This is an aggressive disease with a very rapid rate of progression, and many young children die even before they can reach any medical facility. The scenario of cerebral malaria is even worse in the underprivileged and neglected conditions like ours. The clinical outcome of cerebral malaria is directly related to the optimacity of medical facilities and as Endeshaw and co-workers have noted, the morbidity and mortality of cerebral malaria is increased in suboptimal clinical conditions.